Anthropologie québécoise, études amérindiennes, et la revue "Recherches amérindiennes au Québec" - Gélinas, Claude (Anthropologica, 2022)
The journal Recherches amerindiennes au Quebec was founded in 1971. In the beginning, its founders had three main objectives: they wanted to offer francophone amerindianists an opportunity to publish in their own language; contribute to the knowledge of native cultures of Quebec and give the journal a multidisciplinary status so it could be opened to all individuals working on Native and Inuit topics. An analysis of RAQ contents over the last 30 years shows that if these initial objectives have been achieved, it is because the journal constantly adapted itself to the different ideologies that shaped native studies in Quebec. Moreover, RAQ has always better reflected the state of native studies done in universities than the state of native studies done outside universities, even though the latter has always produced the greater part of our knowledge on native populations.